Gender and Climate Change: The Role of Women in Climate Change Processes - (:unkn) unknown (My University, 2024)
Gender and climate change research has revealed that the causes and effects of climate change differ by gender. Women are affected differently by climate change impacts, and this calls for their participation at the decision-making table in climate change discourse processes. Despite their vulnerable position in society, women are seen as change agents in natural resource management, farming, innovation, and caregiving. As a result, in economies which are heavily natural resource reliant, women are critical for establishing resilient systems and ensuring climate change adaptation. In this review, we hypothesize by answering the question, "What roles do women play in the climate change adaptation and mitigation processes?” We uncover evidence to support the hypothesis that women act as climate change negotiators, clean technology ambassadors, climate-smart agriculture ambassadors, and climate change activists in the climate change processes using a systematic review system meta-analysis inspired by PRISMA and the Publish or Perish review tool as a form of qualitative analysis. We used over 40 pieces of literature to foster the evidence of the study.
Keywords: African Research